HyPro: A Multi-DoF Hybrid-Powered Transradial Robotic Prosthesis - C. L. Semasinghe; R. K. P. S. Ranaweera; J. L. B. Prasanna; H. M. Kandamby; D. G. K. Madusanka; R. A. R. C. Gopura (Journal of Robotics)
This paper proposes a multi-DoF hybrid-powered transradial robotic prosthesis, named HyPro. The HyPro consists of two prosthetic units: hand and wrist that can achieve five grasping patterns such as power grasp, tip grasp, lateral grasp, hook grasp, and index point. It is an underactuated device with 15 degrees of freedom. A hybrid powering concept is proposed and implemented on hand unit of HyPro where the key focus is on restoration of grasp functions of biological hand. A novel underactuated mechanism is introduced to achieve the required hand preshaping for a given grasping pattern using electric power in the pregrasp stage and body power is used in grasp stage to execute the final grasping action with the selected fingers. Unlike existing hybrid prostheses where each of the joints is separately controlled by either electric or body power, the proposed prosthesis is capable of delivering grasping power in combination. The wrist unit of HyPro is designed and developed to achieve flexion-extension and supination-pronation using electric power. Experiments were carried out to evaluate the functionality and performance of the proposed hybrid-powered robotic prosthesis. The results verified the potential of HyPro to perform intended grasping patterns effectively and efficiently.